The role of chromosome changes in the diversification of Passiflora L. (Passifloraceae). Issue 1 (2nd January 2019) - Sader, Mariela A.; Amorim, Bruno S.; Costa, Lucas; Souza, Gustavo; Pedrosa-Harand, Andrea
Abstract : Passiflora L. has more than 575 species distributed especially in the Neotropics. The chromosome number variation in the genus is highly congruent with its main subgenera, but its basic chromosome number ( x ) and the underlying events responsible for this variation have remained controversial. Here, we provide a robust and well-resolved time-calibrated phylogeny that includes 102 taxa, and by means of phylogenetic comparative methods (PCM) we tested the relative importance of polyploidy and dysploidy events to Passiflora karyotype evolution and diversification. Passiflora arose 42.9 Mya, with subgenus diversification at the end of the Palaeogene (Eocene-Oligocene). The basic chromosome number of the genus is proposed as x = 6, and a strong recent diversification found in the Passiflora subgenus (Miocene) correlated to genome size increase and a chromosome change from n = 6 to n = 9 by ascending dysploidy. Polyploidy, conversely, appeared restricted to few lineages, such as Astrophea and Deidamioides subgenera, and did not lead to diversification increases. Our findings suggest that ascending dysploidy provided a great advantage for generating long-term persistent lineages and promoting species diversification. Thus, chromosome numbers/genome size changes may have contributed to morphological/ecological traits that explain the pattern of diversification observed in the genus Passiflora .